2023
DOI: 10.1021/acs.jpclett.3c01491
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Ethylbenzene Conversion on Rutile TiO2(100) via Photocatalysis: The Strong Photon Energy Dependence

Abstract: Direct dehydrogenation of alkanes under mild conditions offers a green route to produce valuable olefins, but realizing C–H bond activation at a low temperature presents a significant challenge. Here, photocatalytic ethylbenzene conversion into styrene has been achieved by one hole on rutile (R)–TiO2(100) at 80 K under 257 and 343 nm irradiation. Although the rates of the initial α-C–H bond activation are nearly the same at the two wavelengths, the rate of the β-C–H bond cleavage is strongly dependent upon hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In order to overcome the consumption of available energy by the IVR process, excitation with higher energy photons may be a feasible way. Referring to the results of the recent photocatalytic conversion of EB into styrene on R-TiO 2 (100), 56 the efficiency of the initial α-C–H bond activation is nearly the same at 257 nm and 343 nm, whereas the rate of the β-C–H bond cleavage was strongly enhanced with the photon energy. In contrast, for C 2 H 6 and C 3 H 8 , 21,25 once the initial C–H bond cleavage was activated by the hole derived from the 355 nm photoexcitation with a lower photon energy, the second dehydrogenation was still accomplished quite easily.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In order to overcome the consumption of available energy by the IVR process, excitation with higher energy photons may be a feasible way. Referring to the results of the recent photocatalytic conversion of EB into styrene on R-TiO 2 (100), 56 the efficiency of the initial α-C–H bond activation is nearly the same at 257 nm and 343 nm, whereas the rate of the β-C–H bond cleavage was strongly enhanced with the photon energy. In contrast, for C 2 H 6 and C 3 H 8 , 21,25 once the initial C–H bond cleavage was activated by the hole derived from the 355 nm photoexcitation with a lower photon energy, the second dehydrogenation was still accomplished quite easily.…”
Section: Resultsmentioning
confidence: 85%
“…This suggested that the photon energy for the C–H bond activation of small alkanes into alkenes via TiO 2 photocatalysis may be utilized more efficiently than that of aromatic EB. 39,56 Furthermore, due to phenyl group substitution, the rate-determining step of the photocatalytic dehydrogenation of hydrocarbons into corresponding alkenes shifts from the initial C–H bond activation to the second further dehydrogenation. 25,39 This result may be more evidence that the IVR process in the larger molecule reduces the available energy for bond breaking.…”
Section: Resultsmentioning
confidence: 99%